Repurposing of atorvastatin emulsomes as a topical antifungal agent - Alaa S. Eita; Amna M. A. Makky; Asem Anter; Islam A. Khalil (Taylor & Francis Group, 2022)
Cutaneous fungal infection therapy confronts several issues concerning skin permeation in addition to drug resistance and adverse effects of conventional drugs. The repurposing strategy is supposed to overcome some of those therapeutic obstacles. Recently, atorvastatin (ATO) revealed antifungal activity. ATO is an antihyperlipidemic drug with pH-dependent solubility, which limits skin permeation. This study aims to improve ATO antifungal activity by encapsulation in an emulsomes (EMLs) system, which seeks to ameliorate skin penetration. Therefore, multiple factors were investigated according to the One-Factor-at-a-Time (OFAT) design to achieve the optimum formula with targeted characteristics. Minimizing particle-size and polydispersity-index, besides elevating zeta-potential (ZP) and entrapment-efficiency were the desirable responses during assessing 11 factors. The selected ATO-EMLs formula (E21) recorded 250.5 nm in particle size, polydispersity index of 0.4, ZP of -25.93 mV, and 83.12% of drug entrapped. Morphological study of E21 revealed spherical core-shell vesicles in nanosize. DSC, XRD, and FTIR were conducted to discover the physicochemical properties and confirm emulsomes formation. Optimized ATO-EMLs slowed drug release rate as only 75% of ATO was released after 72 h. Stability study recommended storage between 2 and 8 °C. The in vivo permeation study remarked a homogeneous penetration of EMLs in different skin layers. The in vivo skin irritation test revealed limited histopathological changes. The in vitro and in vivo microbiological studies demonstrated a good antifungal activity of ATO-EMLs. ATO-EMLs system improved antifungal activity as the MIC values reduced from 650 µg/mL for free ATO to 550 µg/mL for ATO-EMLs. These findings may shed light on ATO as an antifungal drug and nanosystems as a tool to support drug repurposing.